Plant physiology: a primer - Johnson, Giles (Henry Stewart Talks, 2019)
Plants as sessile, usually autotrophic organisms, The photosynthesis process, The transport system in the plant (xylem and phloem), Stomata as a double-edged sword, Acclimation and adaptation of plants to their environment, Symbiotic relationships of plants with fungi and bacteria